Does personality influence workplace bullying and lead to depression among nurses? - Hairul Akmal Mohd Halim,; Fatimah Wati Halim,; Rozainee Khairuddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Workplace bullying is one of the most common work related psychological problems and has been a topic of interest since the 1990s. However, only a few researchers have investigated the influence of personality towards workplace bullying and depression. This study examines the role of personality factors as predictors of workplace bullying and their effects on depression. Structural equation modeling analysis was used to analyze the workplace bullying model. The research involved 340 registered nurses from the public sector. The respondents completed questionnaires on personality factors, workplace bullying, and depression. Results showed that only conscientiousness influenced workplace bullying and neuroticism affected depression directly. Workplace bullying has been found to directly influence depression among nurses. The findings have implications on how workplace bullying plays a key role in the relationship between personality and depression and may serve as a guideline on how to prevent nurses from psychological problems caused by workplace bullying.